Discovery of 3-((3-amino-1H-indazol-4-yl)ethynyl)-N-(4-((4-ethylpiperazin-1-yl)methyl)-3-(trifluoromethyl)phenyl)benzamide (AKE-72), a potent Pan-BCR-ABL inhibitor including the T315I gatekeeper resistant mutant - Ashraf K. El-Damasy; Hyun Ji Kim; Jung Woo Park; Yunju Nam; Wooyoung Hur; Eun-Kyoung Bang; Gyochang Keum (Taylor & Francis Group, 2023)
BCR-ABL inhibition is an effective therapeutic approach for the treatment of chronic myeloid leukaemia (CML). Herein, we report the discovery of AKE-72 (5), a diarylamide 3-aminoindazole, as a potent pan-BCR-ABL inhibitor, including the imatinib-resistant mutant T315I. A focussed array of compounds 4a, 4b, and 5 has been designed based on our previously reported indazole I to improve its BCR-ABLT315I inhibitory activity. Replacing the morpholine moiety of I with the privileged tail (4-ethylpiperazin-1-yl)methyl afforded 5 (AKE-72) with IC50 values of < 0.5 nM, and 9 nM against BCR-ABLWT and BCR-ABLT315I, respectively. Moreover, AKE-72 potently inhibited a panel of other clinically important mutants in single-digit nanomolar IC50 values. AKE-72 elicited remarkable anti-leukemic activity against K-562 cell line (GI50 < 10 nM, TGI = 154 nM). In addition, AKE-72 strongly inhibited the proliferation of Ba/F3 cells expressing native BCR-ABL or its T315I mutant. Overall, AKE-72 may serve as a promising candidate for the treatment of CML, including those harbouring T315I mutation.